The effects of surface tension and wire diameter on the rise velocity of a bubble in a miniature two-phase closed thermosyphon - Lee, Y.-S.; Lee, Y.-P.; Lee, Y. (Elsevier Ltd, 1996)
The rise of a large gas bubble in a miniature two-phase closed thermosyphon with a thin wire insert has been analyzed by the potential flow theory. The effect of the interfacial surface tension is explicitly accounted for by the application of the Kelvin-Laplace equation and solved for the bubble shape. The solution is expressed in terms of the Stokes stream function which consists of an infinite series of Bessel functions. The conditions of the bubble movement in a miniature two-phase closed thermosyphon were theoretically ascertained. The analytical results were compared with the experimental results. Copyright ？ 1996 Elsevier Science Ltd.